Caracterização e avaliação das fibras de Schoenoplectus californicus (C.A. Mey.) Soják para a produção de papéis - Wille, Vania Karine Dick (2014)
Brazil is a major producer of paper, highlighted worldwide for producing and supplying the markets with large volumes of paper packaging, printing and writing paper and cardboard. Although the wood is the main source of raw material used in cellulose industries in Brazil, the use of non-timber fiber may be a satisfactory alternative for manufacturing of papers with different and special properties. In this sense, the objective of this study was to evaluate the productivity, morphology, anatomy and chemical composition of the fibers, as well as the properties of the pulps produced papers of Schoenoplectus californicus (C.A. Mey.) Soják (popularly known as reed), pure or mixed with eucalyptus pulp. We conducted chemical, morphological and productivity analysis. Thus the kraft pulping process and production roles in different treatments were performed. Through research and analysis, it can be noted that reed had low productivity and short fibers. Chemical analysis showed that the fibers have a high level of the reed extractives and silica, which makes it a favorable raw material for pulp production, on the other hand, the kraft pulping process resulted in reed pulp with low contents of hexenuronic acid suitable for the bleaching of pulp factor. The strength properties of the papers were negatively affected by the addition of reed pulp papers and the highest values of bulk and opacity were achieved with the lowest levels of refining of the pulps. It was concluded that reed did not show satisfactory for the production of papers of high strength characteristics.